IMPLEMENTATION OF CIVIC EDUCATION CURRICULUM AT SENIOR SECONDARY SCHOOLS: NEED TO INCORPORATE E-LEARNING STRATEGIES - ABUBAKAR, TAHIR A.; OTENIYA, MOJEED GBENGA (Sokoto Educational Review, 2025)
Success or failure of every education system largely dependants on the quality of implementation of the curriculum. This study is aimed at studying implementation of civic education curriculum at senior secondary schools and the essential needs to incorporate e-learning strategies in order to meet up with the 21st digital era learning system. Senior secondary schools have been for long confronted with several problems which include failure to adequately incorporate e-Learning Strategies as an alternative to the commonly used physical learning situation in the implementation of civic education curiculum. The problem has undoubtedly resulted set back especially during the period which the entire world witnessed Corona Virus global pandemic, and that faults the process of civic education curriculum implementation in our senior seconadry schools. Thus, the quest of alternative to curriculum imlementation becomes necessary as to create enabling and smooth curriculum implementation processes. Therefore,involvement of e-learning in the curriculum implememntaion of civic education becomes paramount importance.in schools. This paper discusses the need to incorporate e-learning teaching in the implementation of Civic Education Curriculum (CEC) as to achieve uninterractive success and achievement of the subject (CEC) in senior secondary schools. The paper also described the concept of civic education, the relevant of e-learning teaching strategies that can be best consider and adopt in the delivery of civic education curriculum at the aforementioned level. Similarly, the paper discussed and higlighted importance and benefits of e-learning in the implementation strategies of civic education curriculum. Neverthelss,the paper proposed some useful and workable suggestions on how best the E-Learning Teaching Strategies can be optimally utilized and handled in the delivery of civic education in senior secondary schools.